The Role of the Bunga Lestari Teacher Activity Center Learning Community in Improving the Competency of Early Childhood Education Educators in Bungah District, Gresik Regency - Rofi'ah, Saidatur; Lestari, Gunarti Dwi; Yusuf, Ali (International Journal of Emerging Research and Review, 2025)
Objective: This study aims to examine the role of the Bunga Lestari Teacher Activity Center (PKG) Learning Community in enhancing the competency of Early Childhood Education (PAUD) educators in Bungah District, Gresik Regency. It focuses on how the learning community contributes to pedagogic, personal, social, and professional competencies of PAUD educators amidst the implementation of the independent curriculum. Method: A qualitative descriptive approach was employed, collecting data through observation, interviews, and documentation among members of the PKG Bunga Lestari community consisting of educators from preschool institutions in Bungah. The study analyzed the forms of competency improvements, the community’s role as a learning platform, and factors supporting or inhibiting its effectiveness.  Results: Findings show that the PKG Bunga Lestari Learning Community effectively facilitates professional development by enabling peer discussion, sharing of best practices, and overcoming challenges related to the independent curriculum. Educators reported improved pedagogical skills and increased confidence in curriculum implementation. The community also helped disseminate government policies related to early childhood education. Novelty: This research contributes novel empirical evidence on the practical impacts of a structured learning community within a rural Indonesian context. It highlights the PKG Bunga Lestari community as a sustainable, collaborative model of strengthens educational policy advocacy and local networking, offering valuable insights for similar educational settings.